AUGMENTED REALITY TECHNOLOGY APPROACH TOWARDS ENGINEERING DRAWING - Mohd Zulfabli Hasan; Nur Ismalina Haris; Nurisah Abdul Wahab@ Wahab; Sahrijan Ahmad; Hashimi Mat Lazim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The technology of the gadgets shows the wave of evolution "Industrial Revolution 4.0" or known as "Industry 4.0â€ has begun. There are 9 pillars of revolution 4.0 and fundamentally, augmented reality is one of the important pillar. Moreover, the Industrial Revolution 4.0 is an innovation that moves from the digital age to the physical cyber era. Consequently, the new field will dominate the world that will focus more on the field of computer science or computing engineering. With the launching of Malaysia Education Development Plan 2015-2025 for higher education steps have been taken to push the Technical and Vocational Education and Training (TVET) which includes special intervention in teaching and learning in this field. Correspondingly, augmented reality being the interactive method of technology that has been hypnotize peoples especially generation Z. In this regard, 21st Century Learning Methods are subjected to the technology based in order to attract the student. Therefore, the researchers have made a study on augmented reality technology approach towards engineering drawing subject among the Mechanical engineering students at Politeknik Tuanku Syed Sirajuddin, Arau, Malaysia in order to study about the impact of AR technology. Pre and post-test has been conducted through this study among 36 first semester students who taking for engineering drawing course. As a result, students have shown an improvement in understanding and assessment performance. Results analysis showed 22% increase in student achievement for excellent grades (90-100), while 39% improvement for Good grades (70-89) whereas moderates grades (40-69) reduced by 58% and weak grade (0-39) grades were abolished 100%. Hence, this study shows that augmented technology was suitable to adapt in 21st century learning method that can be impacted to the students.